Direct Inhibitors of Ras-Effector Protein Interactions - Upadhyaya, Punit; Bedewy, Walaa; Pei, Dehua (Mini Reviews in Medicinal Chemistry, 2016)
Activating Ras mutations are associated with 30% of all human cancers, which often respond poorly to standard therapies. The four Ras isoforms are therefore highly attractive targets for anticancer drug discovery. However, Ras proteins function through protein-protein interactions and their surfaces lack any major pockets for small molecules to bind; as a result they have been declared “undruggable” for the past 30 years. Several breakthroughs during the past few years may finally remove Ras from the list of undruggable proteins. This mini-review discusses the current approaches to developing inhibitors especially cyclic peptides that physically block the interaction between Ras and its downstream effector proteins, which is potentially the most effective approach for treating Ras mutant cancers.
Keywords: Cancer